Public Relations w strukturze organizacji - Bielawski, Piotr (Public relations in the structure of the organization, 2007)
In order to make the public relations a fully useful tool for the organization it is necessary to place properly the PR department within its structure. PR department - when its manager is not a member of the Board - should directly be subordinated to the company’s president. Pacing the PR in the ale marketing, personnel management or administration department, means mostly unconscious decision about giving the information management (PR) up. In such a situation we have only the usage of PR techniques as supportive means for other management disciplines. Marketing and PR department should be placed on the same level of the company structure in order to avoid the domination of one of them. The scope of the PR director should also include the “service” for other departments like personnel management, marketing or legal departments. Efficient PR department ought to create the situation when employing the PR specialist in other departments is not necessary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 256-267